Polyvinyl Alcohol-Anthranilic Acid Composite as Corrosion Inhibitor for Mild Steel - Srimathi, M.; Rajalakshmi, R.; Subhashini, S. (Asian Journal of Chemistry, 2010)
The inhibitive nature of polyvinyl alcohol-anthranilic acid (PVAAA) on the corrosion of mild steel in 1 M HCl solution under various conditions has been investigated by means of weight loss, potentiodynamic polarization and AC impedance methods. The studies show that polyvinyl alcohol-anthranilic acid exhibited excellent inhibition property. The potentiodynamic polarization studies reveal that the polyvinyl alcohol-anthranilic acid acts as a mixed type inhibitor. The adsorption of the polymer on the mild steel surface was found to obey Langmuir and Temkin adsorption isotherms.